(untitled) (Bangladesh Journal of Medical Science, 2024)
Objective: A health problem that is a priority for medical care and treatment for the elderly is pain in the musculoskeletal system. Non-pharmacological management in the form of treating musculoskelatal pain in the elderly, one of which is infrared therapy. Infrared therapy is able to reduce pain in the elderly and requires close supervision because the elderly experience a decrease in skin sensitivity to heat. The effectiveness of reducing pain varies in the elderly. One of the influencing factors is age. This study’s objective is to determine differences in the effectiveness of infrared therapy to reduce musculoskeletal pain in the elderly group. Materials and methods: This study used an experimental research method with a nonrandomized pretestposttest control group design. The research location was conducted at the Posbindu Institut Teknologi Sains dan kesehatan PKU Muhammadiyah Surakarta, in September - October 2022. A sample of 50 elderly people was divided into elderly (> 60 years: 30) and pre-elderly (45-60 years: 20) selected using a purposive technique sampling. The dependent variable is musculoskeletal pain. The independent variable is infrared therapy. Data were analyzed by Wilcoxon and Mann-Whitney test. Results and Discussion: The Wilcoxon test showed that there was an effect of infrared therapy in reducing musculoskeletal pain in the elderly and preelderly groups (p value <0.001 and <0.001). The average reduction in pain in the elderly group = 3.1; SD = 1.3 and pre-elderly = 2.95; SD = 1.2. The Mann-Whitney test showed no difference in reducing musculoskeletal pain using infrared therapy in the elderly and pre-elderly (p = 0.712). Conclusion: Infrared therapy is effective in reducing musculoskeletal pain and reducing musculoskeletal pain for the two elderly groups are similar Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 108-114